Phosphonium cation-based ionic liquids as neat lubricants: Physicochemical and tribological performance. (March 2016) - Hernández Battez, A.; Bartolomé, M.; Blanco, D.; Viesca, J.L.; Fernández-González, A.; González, R.
Abstract: This paper studies physicochemical properties (density, viscosity, corrosion, thermogravimetry, and conductivity) and tribological behavior of five phosphonium cation-based ionic liquids ([P66614 ][BEHP], [P66614 ][C8 C8 PO2 ], [P66614 ][NTf2 ], [P44414 ][DBS], and [P4442 ][DEP]) as neat lubricants within steel–steel contact. A reciprocating ball-on-disc configuration was used to perform tribological tests. Worn surfaces were analyzed by confocal microscopy, SEM, EDS and XPS. Main results showed that: [P66614 ][NTf2 ], [P44414 ][DBS], and [P4442 ][DEP] showed corrosion activity; the ionic liquids with more reactive phosphate type anion ([P66614 ][BEHP] and [P4442 ][DEP]) had the best tribological behavior; the best tribological results were related to the tribofilm formation of two phosphate species. Highlights: The [P66614 ][NTf2 ], [P44414 ][DBS] and [P4442 ][DEP] showed corrosion activity. [P66614 ][BEHP] and [P4442 ][DEP] showed lowest two thermal degradation steps. [P66614 ][BEHP] and [P4442 ][DEP] had the best tribological behavior. Friction and wear reduction of the ionic liquids is related to tribofilm formation. [P66614 ][NTf2 ] and [P4442 ][DEP] showed high conductivity.